Faktor Pendorong dan Penarik Migrasi Penduduk di Perkotaan (Kasus Migran Atambua di Kota Malang) - Agustinus Tedy Loe; Fatima Abdullah; Noeke Chrispur Mardiasih (University Merdeka Malang, 2022)
This study examines the push and pull factors of Atambua migrants in Malang City in the period 1985-2020. This study uses a migration approach that is viewed from two main factors, namely: (i) the push factor from the area of origin; and (ii) the pull factor owned by the destination area. The research location is Malang City as one of the centers of economic activity in East Java. The method used is descriptive narrative, where the data collection uses a questionnaire instrument. This study found that Atambua migrants chose Malang City because of their family and government support, because the majority of Atambua migrants moved to Malang City as a background to pursue higher education. From the driving side, the Atambua area in East Nusa Tenggara (NTT) still has various infrastructure limitations, especially the lack of educational facilities. This finding strengthens the proposition that the existence of basic infrastructure such as educational facilities is one of the strong driving factors in increasing the attractiveness of population migration.